O pensamento de um homileta brasileiro: apresentação e autoavaliação da obra acadêmica, científica e literária de Jilton Moraes - Castro, Jilton Moraes de (2013)
The present text constitutes an overview of the historical context, motivation, objectives, content and relevance of the academic, scientific and literary production of Jilton Moraes de Castro as it concerns the religious field in Latin America. The starting point is a historical view of the sixties and seventies, a time of shortage of literature in the field of Homiletics. As a seminary faculty, the lack of adequate textbook in the classroom coupled with the demands of the students led to the production of the needed textbook. Next, it describes how, after the onset of the first book a trilogy of Homiletics followed. Thirdly, it recounts the origin of five books geared toward the science of preaching, yielding a total of eight volumes in this area of practical theology and Christian preaching, in particular. In the fourth place, it points out to the publication of Homiletics: from research to the pulpit, in Spanish. Fifth, the text provides a glimpse of ten new titles in the pipeline, some of which with input from other researchers on the subject from Brazil and Latin America. Next to last, it mentions the usefulness of the literature published by Jilton Moraes de Castro reaching his birth country, Latin America and the United States of America. Finally, the text concludes with an attempt to answer some questions relevant to the subject: why and what we preach? What is the place of preaching today? As preach this digital generation? How to cristocentricidade must be present in Christian preaching? What characterizes the protestant preaching in Brazil? The theology and practice of preaching in Brazil and Latin America need to be questioned.